Introducción al modelado hidráulico: conceptos básicos y herramientas avanzadas (EPANET, EPA SWMM, HEC-RAS) - Bonilla Granados, Carlos Alexis; Sánchez Tapiero, Diego Iván; Ramón-Valencia, Jarol Derley (Sello Editorial Unipamplona, 2024)
This book, Introduction to Hydraulic Modeling: Basic Concepts and Advanced Tools (EPANET, EPA SWMM, HEC-RAS), offers a comprehensive guide to hydraulic modeling within the fields of civil and environmental engineering. In practical hydraulics, the ability to model water supply networks and urban drainage systems is essential, especially for analyzing, designing, and optimizing solutions to challenges in water supply and sanitation. The book is structured into three chapters, each focused on a specific hydraulic modeling tool. The first chapter centers on the EPANET software, exploring the essential concepts for water network design and applying them in a practical case study. The second chapter addresses EPA SWMM, a tool from the United States Environmental Protection Agency designed for the analysis of urban sewer networks, and guides the reader through the program’s implementation in an applied exercise. The third chapter introduces HEC-RAS software, developed by the United States Army Corps of Engineers, to model the hydraulics of natural and artificial channels and rivers, employing a case study to analyze different flow scenarios in a natural drainage channel. This book is ideal for undergraduate and graduate students in Civil and Environmental Engineering, as well as for professionals seeking in-depth knowledge in hydraulic modeling. In addition to a solid theoretical foundation, each chapter includes practical exercises to apply and reinforce the knowledge gained. With a didactic approach and an emphasis on advanced modeling tools, this work contributes to the continuous learning of hydraulic principles applied to computer-assisted design.